2016
DOI: 10.1038/srep20027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Low-Dose Radiation on Human Neural Progenitor Cells

Abstract: The effects of chronic low-dose radiation on human health have not been well established. Recent studies have revealed that neural progenitor cells are present not only in the fetal brain but also in the adult brain. Since immature cells are generally more radiosensitive, here we investigated the effects of chronic low-dose radiation on cultured human neural progenitor cells (hNPCs) derived from embryonic stem cells. Radiation at low doses of 31, 124 and 496 mGy per 72 h was administered to hNPCs. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…The findings of the present study indicated that low-dose-rate 137 Cs-γ irradiation results in clear inhibition of NGF-induced neurite extension, consistent with the findings of previous reports [ 1 , 2 ]. Furthermore, our results revealed that activation of Rac 1 (a protein that induces neurite extension) is influenced by the irradiation-induced activation of CaMKII, independent of the ERK and Akt pathways.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of the present study indicated that low-dose-rate 137 Cs-γ irradiation results in clear inhibition of NGF-induced neurite extension, consistent with the findings of previous reports [ 1 , 2 ]. Furthermore, our results revealed that activation of Rac 1 (a protein that induces neurite extension) is influenced by the irradiation-induced activation of CaMKII, independent of the ERK and Akt pathways.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of low-dose or low-dose-rate irradiation on neuronal cells have drawn increasing attention in recent years. Research has indicated that chronic irradiation with low-dose-rate 137 Cs-γ rays inhibits the differentiation of human neural progenitor cells in a dose-dependent manner [ 1 ]. Furthermore, such chronic irradiation has been shown to influence the expression of proteins associated with cell adhesion, apoptosis, and metabolism, among other functions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dose radiation effects were previously shown to cause aberrant gene expression in various cells and tissues (Luzhna and Kovalchuk, 2014 ; Sokolov et al, 2015 ; Katsura et al, 2016 ; Sokolov and Neumann, 2016 ). Therefore, we proceeded to analyze the global gene expression profiles of the hippocampus and PFC tissues of control and scatter-exposed male and female rats.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover the DNA double strand breaks and apoptosis were induced in the ventricular and subventricular zones of mouse embryo [16]. It was also shown that 496 mGy of irradiation caused a significant decrease in the MAP-2 positive cells and neurite length [17]. Thus understanding of the differences between effects induced by different doses and dose-rates of radiation and the impact they may have on neuronal cancer stem cells is crucial for properly predicting the risks of low-dose radiation on the NSC potential to differentiate.…”
Section: • Low-dose Effect On Nscmentioning
confidence: 94%